LEADERSHIP BLINDSPOTS. Issue 100 (18th June 2021) - Goleman, Daniel
Abstract: The author notes that leaders, and by extension businesses and other organizations, must take in information with deep understanding and be prepared for nimble responses. Yet this is hampered by what the author calls "blindspots, " which are "crucial aspects of organizational reality that leaders fail to see or to regard as important." Goleman has done extensive work for years on emotional intelligence and notes that it "entails two varieties of a leader's attention: on one's self, and on others." But he also raises a third level, that of the system in which a leader operates, and another area where blindspots can emerge. He points out hidden opportunities and writes about recent research on the concept of caste, and how it applies to the United States, and not just to countries like India. He asserts that leaders "must unveil and then lead efforts to overcome systemic bias in your organization, whether against African‐Americans, Hispanics, Asians, women, or others." He also writes about leadership's roles and opportunities for dealing with our environmental crisis and the different approaches and awareness level of younger and older generations. "The final ingredient here, " Goleman writes, "will be innovation, that mark of agility."